Camping for Kids - Howard, Melanie A. (Mankato, Minn. : Capstone Press, 2013)
"Explores the popular activity of camping, including tips, techniques, conservation, and specific gear needed"--Provided by publisher.
Includes bibliographical references and index.
Accelerated Reader AR
Keywords: Camping -- Juvenile literature